2021
DOI: 10.29040/ijebar.v5i1.1721
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Chinese Customers’ Online Purchase Intention: The Case Study of JINGDONG.COM Online Shopping’s Customer in China

Abstract: In the past two decades, the development of China's Internet industry has been very rapid. Many service industries around the Internet have also been on the rise, of which, online shopping has become the fastest growing Internet industry chain. This study will focus on analyzing customer’s online purchase intentions, the researchers found four variables that have a relationship with customers online purchase intention. Primary data of this research were collected by online and offline questionnaires which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
0
0
2
Order By: Relevance
“…Therefore, a good reputation for the seller will greatly affect the buyer's purchase intention. The results of this study are consistent with the previous studies by Zhen et al (2021) which shows that consumers may be aware of online reputation sellers. They also revealed that perceived reputation has a high correlation with online purchase intention.…”
Section: Effects Of Product Quality Service Quality Price Familiarity...supporting
confidence: 93%
“…Therefore, a good reputation for the seller will greatly affect the buyer's purchase intention. The results of this study are consistent with the previous studies by Zhen et al (2021) which shows that consumers may be aware of online reputation sellers. They also revealed that perceived reputation has a high correlation with online purchase intention.…”
Section: Effects Of Product Quality Service Quality Price Familiarity...supporting
confidence: 93%
“…Berdasarkan penelitian yang dilaksanakan Zhen et al, (2021) menghasilkan persepsi reputasi dan niat beli online pelanggan, sikap pelanggan dan niat beli online pelanggan yang melibatkan 300 pengisi kuesioner. Penelitian yang dilakukan Shi et al, (2018) bertujuan untuk mengintegrasikan bias termasuk inersia yang disengaja pelanggan dan cognitive lock dengan kepercayaan dan komitmen pelanggan dalam perspektif.…”
Section: Loyalitas Pelanggan Terhadap Niat Beliunclassified
“…Serta hubungan antara niat beli ulang dan loyalitas pelanggan memiliki pengaruh sebesar 0,664 dengan indikator paling utama atau berpengaruh yaitu loyalitas pelanggan. Hasil ini sesuai dengan penelitian yang pernah dilakukan oleh Hallikainen dan Laukkanen (2011), Zhen et al, (2021) serta Shi et al, (2021). Berdasarkan pembahasan di atas dapat menunjukkan bahwa loyalitas pelanggan dapat menimbulkan niat beli ulang.…”
Section: Pembahasanunclassified